Respuesta :
Answer:
3 (x - 1)
Step-by-step explanation:
Simplify the following:
3 - 2 (x + 1) + 5 x - 4
Grouping like terms, 3 - 2 (x + 1) + 5 x - 4 = -2 (x + 1) + 5 x + (3 - 4):
-2 (x + 1) + 5 x + (3 - 4)
3 - 4 = -1:
-2 (x + 1) + 5 x + -1
-2 (x + 1) = -2 x - 2:
5 x + -2 x - 2 - 1
Grouping like terms, 5 x - 2 x - 2 - 1 = (5 x - 2 x) + (-2 - 1):
(5 x - 2 x) + (-2 - 1)
5 x - 2 x = 3 x:
3 x + (-2 - 1)
-2 - 1 = -3:
3 x + -3
Factor 3 out of 3 x - 3:
Answer: 3 (x - 1)
3-2(x+1) + (5x-4)
pretend that there is a +1 in front of the second bracket
3-2(x+1) +1 (5x-4)
multiply the first bracket by -2
(-2)(x)=-2x
(-2)(1)=-2
multiply the second bracket by +1
(1)(5x)=5x
(1)(-4)=-4
3-2x-2+5x-4
-2x+5x+3-2-4 ( combine like terms)
3x+3-2-4
3x+1-4
Answer:
3x-3